Aging-Related Vascular Inflammation: Giant Cell Arteritis and Neurological Disorders - Watanabe, Ryu; Hashimoto, Motomu (Frontiers in Aging Neuroscience, 2022)
Aging is characterized by the functional decline of the immune system and constitutes the primary risk factor for infectious diseases, cardiovascular disorders, cancer, and neurodegenerative disorders. Blood vessels are immune-privileged sites and consist of endothelial cells, vascular smooth muscle cells, macrophages, dendritic cells, fibroblasts, and pericytes, among others. Aging also termed senescence inevitably affects blood vessels, making them vulnerable to inflammation. Atherosclerosis causes low-grade inflammation from the endothelial side; whereas giant cell arteritis (GCA) causes intense inflammation from the adventitial side. GCA is the most common autoimmune vasculitis in the elderly characterized by the formation of granulomas composed of T cells and macrophages in medium- and large-sized vessels. Recent studies explored the pathophysiology of GCA at unprecedented resolutions, and shed new light on cellular signaling pathways and metabolic fitness in wall-destructive T cells and macrophages. Moreover, recent reports have revealed that not only can cerebrovascular disorders, such as stroke and ischemic optic neuropathy, be initial or coexistent manifestations of GCA, but the same is true for dementia and neurodegenerative disorders. In this review, we first outline how aging affects vascular homeostasis. Subsequently, we review the updated pathophysiology of GCA and explain the similarities and differences between vascular aging and GCA. Then, we introduce the possible link between T cell aging, neurological aging, and GCA. Finally, we discuss therapeutic strategies targeting both senescence and vascular inflammation.